Precedent, Compliance, and Change in Customary International Law: An Explanatory Theory. Issue 3 (July 2014) - Verdier, Pierre-Hugues; Voeten, Erik
Abstract : Customary international law (CIL) is widely recognized as a fundamental source of international law. While its continued significance in the age of treaties was once contested, it is now generally accepted that CIL remains a vital element of the international legal order. Yet CIL is also plagued with conceptual and practical difficulties, which have led critics to challenge its coherence and legitimacy. In particular, critics of CIL have argued that it does not meaningfully affect state behavior. Traditional CIL scholarship is ill equipped to answer such criticism because its objectives are doctrinal or normative—namely, to identify, interpret, and apply CIL rules, or to argue for desirable changes in CIL. For the most part, that scholarship does not propose an explanatory theory in the social scientific sense, which would articulate how CIL works, why states comply, and why and how rules change.